(ENT 300) Business Model Canvas: Mienne Collection/ Nurul Aida Natasha Ahmad Rofiai - Ahmad Rofiai, Nurul Aida Natasha (2020)
In this Business Canvas Report, we will be discussing on the 9 elements which is Value proposition, the Customer segmentation, how we want to manage our relationship with our customer and our Channel distribution. We will also talk about the key resources, key activities and our key partners. Moreover, we will explain more about the cost structure and the revenue stream of the company. Business Model Canvas can be used to visualize such customer expectations and market problems. This enables us to understand the true value of the proposed solution. Business Model Canvas is used to validate the market significance of our product. Mienne Collection is a footwear brand that give the most elegant and comfortable shoes to our customer. Our main concept is by letting our customer to customized their shoes as what they prefer it to be. We will give the opportunity for our customer to pick a design that we have and redesign the shape of the shoes or resize it according to their comfortability. For example, they can expand the base of their shoes or even change the height of the heels. However, we will also provide a ready-made shoe for our customer that is comfortable and satisfied with our design and the given sizes of the shoes. The reason why we decided to go with this concept is because every person have different size of feet and flaws. So, we will help them to feel complete by wearing our shoes. Mienne is mine in French and the reason why we decided to go with this brand name is because we want to make our customer to feel satisfied and complete while wearing our shoes and tell others that this shoe is mine.